Response and recovery of grassland plant communities exposed to multiyear drought differs across a precipitation gradient - Ross, Maggie, author; Smith, Melinda D., advisor; Knapp, Alan, committee member; Havrilla, Caroline, committee member; Wilkins, Kate, committee member (Colorado State University. Libraries, 2022)
Drought events are expected to increase in grassland ecosystems in many regions of globe due to climate change. Much is known about the effects of drought on grassland plant communities, yet it is difficult to compare responses across different grassland ecosystems because studies impose drought with varying characteristics. Further, few studies have documented plant community recovery, even though the impacts of drought can persist for multiple years. We experimentally imposed four years of extreme, growing season drought at four sites representing the major Central US grassland types (shortgrass steppe, mixed grass prairie, tall grass prairie) spanning a precipitation gradient. Growing season drought was imposed in two ways: 1) by reducing each rainfall event by 66% (chronic) or 2) by completely excluding rainfall until a similar reduction in precipitation as the chronic treatment was achieved (intense). Plant community responses to the two drought treatments were monitored for each year of the four-year drought treatments and four years following the drought to assess recovery. Overall, plant communities at the drier sites responded sooner to drought and took longer to recovery than the wetter sites. Plant composition was altered at all sites, which was largely driven by shifts in the dominant C3-C4 grasses and subsequent species reordering and to a lesser extent by changes in richness in evenness. There was a significant decrease in C4 graminoid abundance in response to drought at all sites with a corresponding increase of C3 annual grasses during the drought at the mixed grass sites but not until the recovery period at the shortgrass steppe. Cheatgrass (Bromus tectorum) invaded the shortgrass steppe during the drought and proliferated during the recovery period, which likely pushed the communities into an alternate state, and inhibited recovery after four years of ambient conditions. The northern mixed grass prairie also did not fully recovery after four years, which indicates that full plant community recovery can extend longer than the drought itself at these drier sites. While there is some indication that intense drought had a greater impact on communities than chronic drought, there is limited evidence to suggest that drought type significantly influenced plant community responses or recovery. These findings indicate that while the shortgrass steppe is water limited with drought adapted species, these xeric grassland plant communities are less resistant and resilient to multiyear drought than those in mesic grasslands.
Keywords: grasslands; recovery; plant community; drought